Distal Radius Fractures Current Concepts - Hove, Leiv M.; Lindau, Tommy; Hølmer, Per (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Distal radial fractures are still puzzling us 200 years after Colles' classic description. Despite the advent of various new imaging techniques, including 3D CT, the availability of diagnostic adjuncts such as arthroscopy, and treatment options that include more than 30 different volar locking plates, the rate of unsatisfactory treatment results remains very high. Furthermore, while we are aware of more associated injuries, such as carpal ligament tears and injuries to the radioulnar ligament (TFCC), there is still intense debate on the relevance of these injuries. This textbook aims to provide the reader with a complete understanding of distal radius fractures, their inherent problems, and how to manage them successfully. It is written by widely published experts from a part of the globe where distal radius fractures are very common, especially during the winter months. Clear guidance is provided on diagnostic imaging, classification, and assessment of fracture instability. The complete spectrum of operative and nonoperative treatment options are then clearly explained with the aid of step-by-step illustrations. Extensive information is also provided on complications and their treatment. Both students and experienced practitioners will find this book to be an enlightening, practice-oriented reference on the management of these challenging fractures.